68. Defective Motor Cortex Plasticity in juvenile myoclonic epilepsy. Issue 12 (December 2016) - Pizzamiglio, C.; Strigaro, G.; Falletta, L.; Tondo, G.; Barbero, P.; Varrasi, C.; Cantello, R.
Abstract : Abnormal cortical plasticity has been hypothesized to play a crucial role in the pathogenesis of juvenile myoclonic epilepsy (JME). We used an excitatory paired associative stimulation (PAS) paradigm to study motor cortex plasticity in patients with JME. Twelve adult patients with JME were compared with 13 healthy subjects (HS) of similar age and sex. PAS consisted of 180 electrical stimuli of the right median nerve paired with a single transcranial magnetic stimulation (TMS) stimulus over the hotspot of right abductor pollicis brevis (APB) at an ISI of 25 ms (PAS25). We measured motor evoked potentials (MEPs) before and after each intervention for up to 30 min. Data entered repetitive measure ANOVAs. In HS the PAS25 protocol was followed by a significant increase of the MEP amplitude (p < 0.001). In patients with JME, the MEP amplitude did not change. We suggest that a defective motor cortex plasticity may play a role in the pathogenesis of JME and it may be involved in the development of myoclonus in these patients.